Why Does the Health of Immigrants Deteriorate? Evidence from Birth Records - Osea Giuntella (Institute for the Study of Labor (IZA), 2013)
Despite their lower socioeconomic status, Hispanic immigrants in the United States initially have better health outcomes than natives. Paradoxically while second-generation immigrants assimilate socio-economically, their health deteriorates. I show that a model of selection and intergenerational transmission of health reverses the apparent paradox, predicting a worse deterioration than the one observed in the data. While higher incidence of risk factors and acculturation are associated with poorer health, the reverse paradox is explained by the relative persistence in healthy behaviors among Hispanics. These effects hold true even in a subset of siblings, and holding constant grandmother-fixed effects.
Keywords: I10; J15; 330; birth outcomes; birthweight; intermarriage; risky behaviors; siblings; Latino paradox